De Novo Truncating Variants in ASXL2 Are Associated with a Unique and Recognizable Clinical Phenotype - Pena, Loren D.M.; Hempel, Maja; McLaughlin, Heather M.; Cho, Megan; Stong, Nicholas; Shuss, Christine M.; Burrage, Lindsay C.; Dhar, Shweta U.; Emrick, Lisa T.; Graham, Brett H.; Lalani, Seema R.; Lewis, Richard A.; et al. (American journal of human genetics, 2016)
The ASXL genes (ASXL1, ASXL2, and ASXL3) participate in body patterning during embryogenesis and encode proteins involved in epigenetic regulation and assembly of transcription factors to specific genomic loci. Germline de novo truncating variants in ASXL1 and ASXL3 have been respectively implicated in causing Bohring-Opitz and Bainbridge-Ropers syndromes, which result in overlapping features of severe intellectual disability and dysmorphic features. ASXL2 has not yet been associated with a human Mendelian disorder. In this study, we performed whole-exome sequencing in six unrelated probands with developmental delay, macrocephaly, and dysmorphic features. All six had de novo truncating variants in ASXL2. A careful review enabled the recognition of a specific phenotype consisting of macrocephaly, prominent eyes, arched eyebrows, hypertelorism, a glabellar nevus flammeus, neonatal feeding difficulties, hypotonia, and developmental disabilities. Although overlapping features with Bohring-Opitz and Bainbridge-Ropers syndromes exist, features that distinguish the ASXL2-associated condition from ASXL1- and ASXL3-related disorders are macrocephaly, absence of growth retardation, and more variability in the degree of intellectual disabilities. We were also able to demonstrate with mRNA studies that these variants are likely to exert a dominant-negative effect, given that both alleles are expressed in blood and the mutated ASXL2 transcripts escape nonsense-mediated decay. In conclusion, de novo truncating variants in ASXL2 underlie a neurodevelopmental syndrome with a clinically recognizable phenotype. This report expands the germline disorders that are linked to the ASXL genes.